Functional response traits in relation to land use change in the Montado - Castro, Helena; Lehsten, Veiko; Lavorel, Sandra; Freitas, Helena (Agriculture, Ecosystems & Environment, 2010)
The socio-economic changes of the last decades have resulted in changes in traditional land uses with consequent abandonment of large farmland areas in the Mediterranean region. We assessed the response of species richness and composition, and species functional traits to decreasing land use intensity in a Montado system, an agro-pastoral system characteristic of the Alentejo, Southern Portugal. Additionally, we investigated whether plant functional types can be established based on the response to decreasing land use intensity in these systems. Consistent with previous studies, species richness decreased sharply after land abandonment, and this was associated with a strong turnover in species composition from grazed to abandoned sites as the vegetation changed from herbaceous to shrub dominated communities. Pronounced differences in functional traits were found for different successional stages. Therophyte life form, short plant height, high speciﬁc leaf area (SLA), low leaf dry matter content (LDMC) and small seeds with dispersal structures were dominant in grazed plots. Within abandoned plots, chamaephytes dominated in plots abandoned for 10–15 years and decreased in favour of nanophanerophytes in plots abandoned for 20–30 years. Plant height, LDMC and seed mass increased with abandonment time while SLA decreased. Functional response groups sufﬁcient to describe vegetation change were identiﬁed combining life form and SLA. Therophytes with medium SLA were the dominant functional group in grazed areas, while nanophanerophytes with medium or low SLA were associated with later phases of abandonment. At intermediate stages of succession the dominant group was chamaephytes with medium SLA but functional diversity was highest as all the groups, except hemicryptophytes with medium SLA, were represented. These changes in functional composition can be translated into effects on key ecosystem properties. The increase in LDMC indicates an increase in ﬂammability while trends in both LDMC and SLA suggest decreased decomposition, and thereby carbon and nutrient cycling. These will need to be considered in combination with consequences for other ecosystem properties for future management.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Fourth-corner method; Functional groups; functional traits; Mediterranean; Null model; Plant; Secondary succession